Estrategia didáctica de aprendizaje basado en problemas para la mejora del proceso de enseñanza de la lengua y la literatura en la unidad educativa intercultural bilingüe “Monseñor Leonidas Proaño”, Riobamba. - Chafla Telenchano, Alba Marina (2023)
The present research refers to the analysis of problem-based learning (PBL) as a didactic strategy for improving the teaching process of language and literature in the Intercultural Bilingual Educational Unit “Monseñor Leonidas Proaño” Riobamba, considering that teachers do not apply the PBL at the time of teaching the language and literature class. The research was instituted as a methodological framework field study, and surveys were carried out among the 35 main stakeholders. This execution is carried out in person, following the agreed parameters for both teachers and students, in a non-probabilistic intentional sample. For this reason, the research is documentary-type, with a quantitative approach. The aspect investigated in this work determines as a conclusion that the majority of teachers lack methodologies that encourage the learning of language and literature in students, due to a lack of specialized teachers; Consequently, students mention having antipathy towards the field of literature. However, the students claimed to know empirically the PBL methodology, since teachers of other subjects applied it as an active feedback method posing a problem for collective resolution.